The Liberation Struggle in Cyprus and the Greek-Cypriot Press: The Positions of the Leading Greek-Cypriot Press in 1957-1960. The Caseof “Eleftheria” Newspaper - Antoniades, Euripides (My University, 2015)
Little is known of the relationship between the anticolonial movement in Cyprus and the role of the Greek-Cypriot press The lack of prior work is a major obstacle and a challenge for communication, media and/or social movements researchers who have no empirical knowledge-base on which to found contemporary studies. The archival material is vast, while at the same time the researcher is confronted with various problems, such as the choice of methodology and testimonials. In a bid to address this absence, this paper presents the preliminary findings of a study dealing with the Liberation Movement of Cyprus (EOKA) and how this was depicted through the Greek-Cypriot press. The period under study is 1957 to 1960, which is when the EOKA movement was active. Based on a content analysis this study investigates the positions of three leading Greek-Cypriot newspapers of that period and aims to present the positions of each newspaper at the level of policy towards the liberation movement. The study finds that each newspaper had its own political approach (agenda – settings), framework (framing) and mediation. Preliminary findings suggest that the Greek-Cypriot press under the colonial regime presented the liberation and the “enosis” movement more in its news-articlesreports and less in opinion articles and commentaries. The study further reveals that journalists’ articles were mostly unsigned. These observations illustrate that one consequence of the politically explosive situation in Cyprus was that journalists were reluctant to take sides for or against the leaders of the liberation movement.
Keywords: Greek-Cypriot press; Liberation Movement of Cyprus; Liberation movement